Diagnostic Accuracy of Ultrasonography in Acute Abdomen Cases - Naveed, Md Amer; Wasiq, Mohammed Umer (Asian Journal of Medical Radiological Research, 2020)
Background: Ultrasonography is an easy to use, cheap and reliable imaging modality. It involves minimal radiation exposure and can predict need for surgical intervention in most of the cases. Acute abdomen is an emergency condition which in most of the cases requires surgical intervention. Ultrasound evaluation can prove to be of much use in such cases. Aims and Objectives: The aim of the present study was to evaluate the diagnostic accuracy of Ultrasonography in cases of acute abdomen. Subjects and Methods: All the cases of acute abdomen presenting to the ER which were sonographically evaluated were included in our study. The USG findings were correlated with laparoscopic findings. The data was collected in MS Excel and presented as numbers and percentages in the form of tables and figures. Sensitivity, Specificity were calculated and analysed. Results: There was an equal gender distribution in our study. Tenderness was the most common clinical feature and observed in 86% of the study population. This was followed by abdominal pain, which was observed in 81% of patients. Fever was a symptom in almost 64% of patients. Rigidity was depicted in 59% patients. 54% patients complained of vomiting. Abdominal Distension was observed in 14% of the study population. The sensitivity of USG in diagnosis of Acute Appendicitis, Acute Pancreatitis, Cholecystitis, Liver Abscess and Renal Calculi was 100%. The specificity of USG in diagnosis of Acute Appendicitis, Acute Pancreatitis, Liver Abscess and Renal Calculi was 100%. Conclusion: Ultrasound abdomen has good diagnostic accuracy in acute abdomen cases and can be helpful in evaluation of most of the acute abdomen cases presenting to the Emergency Room